Vocês, humildes, podem ficar tranquilos: soberania interna no Projeto Nacional de Juarez Távora - Toledo, José Paulo (2022)
This thesis seeks to explore the Brazilian military political thought, analyzing, to achieve this goal, the national project systematized by one of the main military-intellectuals of the Brazilian Army during the 20th century: Juarez Távora. To this end, from a broad reading of the author's work and context, this research analyzes Juarez Távora's political thought, understanding how he narrates the trajectory of his life, based on the 3-volume autobiographical series Uma Vida e Muitas Lutas (1974ª; 1974b; 1977), and describes his national project, observing this development in particular in the most articulate and synthetic of his works: Organization for Brazil (1959). In the quest to understand the Tavorian national project, it is observed where the author located the locus of sovereignty and decision-making power enabled to decide the definition of which national project to follow. The central and articulating concept of the analysis is that of sovereignty, according to the keys of analysis developed in this work: national sovereignty, popular sovereignty, state sovereignty, as described by Grimm in Sovereignty: the Origin and Future of a Political and Legal Concept (2015) and exceptional sovereignty, coined from the text Political Theology: Four Chapters on the Concept of Sovereignty by Carl Schmitt (1985).